Constitutive expression of the sRNA GadY decreases acetate production and improves E. coli growth. Issue 1 (December 2015) - Negrete, Alejandro; Shiloach, Joseph
Abstract Background Escherichia coli responds to acid stress by applying various physiological, metabolic, and proton-consuming mechanisms depending on the growth media composition, cell density, growth phase, pH, and aerobic or anaerobic growth conditions. It was reported that at mild acidic conditions (pH 5.8), the Hfq-associated sRNA GadY is activated. It was also reported that the two decarboxylase systems—the lysine decarboxylase system (LDS) and the glutamate decarboxylase system (GDS)—are activated to maintain intracellular balance of protons. The purpose of this study was to establish the role of GadY in high density growth ofE. coli and to evaluate the possibility of using this small RNA to create an acid-resistant strain suitable for industrial applications. Results ParentalE. coli K-12 and constitutively expressing GadY strains were grown to high cell densities in a bioreactor at pH 7.0 and pH 6.0. At pH 7.0, both strains grew to similar cell densities of 43 OD, but the constitutively expressing GadY strain produced around 6 g/L acetate compared with 10 g/L by the parental strain. At pH 6.0, the parental strain grew to an OD of 20 and produced 10 g/L of acetate while the GadY strain grew to an average OD of 31 and produced 4 g/L acetate. After analyzing 17 genes associated with acid stress, it was found that at pH 7.0 LDS was expressed in the early exponential phase and GDS was expressed in the late exponential phase in both strains. However, at pH.6.0, GDS was expressed in the late exponential phase only in the parental strain and not in the constitutively expressing GadY strain, while there was no difference in the LDS expression pattern; it was expressed in the early exponential phase in both strains. This indicates that GadY affects GDS expression at low pH since the GDS was not detected in the GadY strain at pH 6.0. Conclusions The constitutive expression of GadY improvesE. coli growth at pH 6.0 by deactivating the expression of the GDS in the late exponential growth phase. The expression of GadY also decreases acetate production regardless of pH, which decreases the inhibitory effect of this acid on bacterial growth.